2017
DOI: 10.1515/secm-2016-0243
|View full text |Cite
|
Sign up to set email alerts
|

Synergy of cashew nut shell filler on tribological behaviors of natural-fiber-reinforced epoxy composite

Abstract: The aim of this work is to investigate the adhesive dry sliding wear and friction performance of biodegradable cashew nut shell (CNS)-filler-reinforced epoxy composite. The composites are prepared with 5, 10, 15, 20, 25, 30, 35, and 40 weight content of CNS filler. Experiments were conducted to perform the required measurements. The results show that the specific wear rates and frictional coefficients are found lower at 30% untreated and treated CNS-containing composites. The NaOH-treated CNS filler composites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…On the other hand, YM, hardness, and storage modulus (SM) were increased; the authors claim that this is due to the catalytic effect of OH groups present in fibers on the epoxy reaction kinetics, which may result in a higher crosslink density of the samples. The thermal stability of the composites (5% mass loss, 10% mass loss, and residual mass) was also increased due to the higher thermal Sathishkumar et al [44] studied the dry sliding wear and friction performance of epoxy composites containing cashew nutshell powder. The cashew nutshell powder was prepared from cashew nut seed, and the powder was treated with 5% NaOH solution to remove the weak amorphous phase from it.…”
Section: Post-agricultural Waste Powder Materials Filled Epoxy Composites (Seed and Fruits)mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, YM, hardness, and storage modulus (SM) were increased; the authors claim that this is due to the catalytic effect of OH groups present in fibers on the epoxy reaction kinetics, which may result in a higher crosslink density of the samples. The thermal stability of the composites (5% mass loss, 10% mass loss, and residual mass) was also increased due to the higher thermal Sathishkumar et al [44] studied the dry sliding wear and friction performance of epoxy composites containing cashew nutshell powder. The cashew nutshell powder was prepared from cashew nut seed, and the powder was treated with 5% NaOH solution to remove the weak amorphous phase from it.…”
Section: Post-agricultural Waste Powder Materials Filled Epoxy Composites (Seed and Fruits)mentioning
confidence: 99%
“…The photograph of wood apple fruit and wood apple shell, SEM images of the wood apple shell particles, and erosion wear behavior of the composites at different impingement angles are shown in Figure 5. Sathishkumar et al [44] studied the dry sliding wear and friction performance of epoxy composites containing cashew nutshell powder. The cashew nutshell powder was prepared from cashew nut seed, and the powder was treated with 5% NaOH solution to remove the weak amorphous phase from it.…”
Section: Post-agricultural Waste Powder Materials Filled Epoxy Composites (Seed and Fruits)mentioning
confidence: 99%
“…[2][3][4] Presently, nutshells in the form of particles as a filler material in a polymeric resin are of interest among the scientific community. Almond shell, [5,6] argan nutshell, [7,8] cashew nutshell, [9,10] coconut shell, [11,12] Doum palm shell, [13,14] hazelnut shell, [15,16] palm kernel shell, [17,18] peanut shell, [19,20] pistachio shell [21,22] and walnut shell [1,23] are the nutshells explored by the scientific community as a filler material for different applications.…”
Section: Introductionmentioning
confidence: 99%
“…Reinforcing of epoxy resins by means of good mechanical, thermal electrical and chemical fibers like basalt, glass, carbon and other specific natural fibers is a popular way to improve the properties of the brittle epoxy matrix [13][14][15][26][27][28]. Siva et al [16] concluded that using of cashew nut shell, hazelnut shell or basalt fiber as epoxy composite reinforcements improved its thermal and mechanical properties. Even though epoxy composites depict encouraged tribological performance it remains difficult to recycle.…”
Section: Introductionmentioning
confidence: 99%